T cell cutaneous lymphoma panniculitis type – A clinical case - Antunes, Marisa (2004)
T cell cutaneous lymphoma (T.C.C.L.), panniculitis type, is a rare malignancy of postthymic T cells. A clinical case of a twenty-three year old, female patient, with a five-year evolution of recurret subcutaneous nodules and, later on, hepatosplenomegaly and fever is presented. The diagnosis was only possible with repeated cutaneous byopsies and in late stage of the disease. The patient died following a fatal and rapid leukemia transformation of the lymphoma. Often, the histological aspects of the skin,in early stages of T.C.C.L., does not reveal malignant characteristics. The diagnosis is frequently delayed due to lack of symptoms and dubious hystology, contribuing to the late institution of therapy. The differential diagnosis of T.C.C.L. is established with cutaneous manifestations of autoimmune diseases and end-stage Blastic NK lymphoma, requiring sofisticated laboratorial techniques such as skin, bone marrow and peripheral blood immunophenotyping.